Aroma Volatile Composition of Millingtonia hortensis Linn. F. Flower Growing in Chiang Rai, Thailand - Thongpoon, C.; Machan, T. (Asian Journal of Chemistry, 2015)
First report on the study of the aroma volatile components of the fresh Millingtonia hortensis Linn. F. flower growing in Chiang Rai, Thailand is described. The volatiles of fresh M. hortensis flower were extracted by maceration in petroleum ether at room temperature for 12 h. After removing of the solvent under reduced pressure yielded light yellow semi-solid volatile crude was obtained. The crude was redissolved in ethanol followed by filtration and evaporation to obtain the M. hortensis absolute (0.02 %). The preliminary sensory evaluation showed that the scent of the obtained absolute was the closest to the fresh flower. The volatile compositions were investigated by GC-MS technique. Twenty seven compounds have been identified and accounted for 86 % of the chromatographable components, with solanesol (25.72 %), trans-farnesol (19.71 %), nerolidol (8.54 %), palmetic acid (6.77 %), vanillin (6.20 %), oleic acid (4.54 %), linoleic acid (3.87 %), L-linalool (3.37 %), 1-octen-3-ol (1.67 %), a-farnesene (1.22 %) and methyl salicylate (1.03 %) respectively, as the major constituents.